Optoelectronic response of a WS2 tubular p-n junction. (10th April 2018) - Zhang, Y J; Onga, M; Qin, F; Shi, W; Zak, A; Tenne, R; Smet, J; Iwasa, Y
Abstract: Due to their favourable and rich electronic and optical properties, group-VI-B transition-metal dichalcogenides (TMDs) have attracted considerable interest. They have earned their position in the materials portfolio of the spintronics and valleytronics communities. The electrical performance of TMDs is enhanced by rolling up the two-dimensional (2D) sheets to form quasi-one-dimensional (1D) tubular structures. The fabrication of p-n junctions out of these tubular TMDs would boost their potential for optoelectronic devices as such junctions represent a fundamental building block. Here, we report the realization of a p-n junction out of a single, isolated WS2 -nanotube (WS2 -NT). Light-emitting diode operation and photovoltaic behaviour were observed based on such p-n junctions. The emitted light as well as the photovoltaic effect exhibit strong linear polarization characteristics due to the quasi-1D nature. The external quantum efficiency for the photovoltaic effect reaches a value as high as 4.8%, exceeding by far that of 2D TMDs and even approaching the internal quantum efficiency of the 2D TMDs. This efficiency improvement indicates that TMD nanotubes are superior candidates over 2D TMDs for optoelectronic applications.